Three-body recombination in cold helium--helium--alkali-metal-atom collisions - Suno, Hiroya; Esry, B. D. (My University, 2009)
Three-body recombination in helium-helium–alkali-metal collisions at cold temperatures is studied using the adiabatic hyperspherical representation. The rates for the three-body recombination processes 4He+4He+X→4He+4HeX and 4He+4He+X→4He2+X, with X=7Li, 23Na, 39K, 85Rb, and 133Cs, are calculated at nonzero collision energies by including not only zero total angular momentum, J=0, states but also J>0 states. The three-body recombination rates show a relatively weak dependence on the alkali-metal species, differing from each other only by about one order of magnitude, except for the 4He-4He-23Na system.